Macroeconomic Factors and the Indian Stock Market: Exploring Long and Short Run Relationships - Kotha, Kiran Kumar; Sahu, Bhawna (International Journal of Economics and Financial Issues, 2016)
The rapid growth of Indian economy during the last two decades raises empirical questions regarding the fundamental connection between stock price and key macroeconomic indicators. This paper aims to examine long and short run relations between selected macroeconomic indicators and stock market returns with reference to India. This study employs monthly data from July 2001 to July 2015 since major stock market reforms viz., ban of Badla system, introduction of rolling settlement and introduction of stock derivatives, were all implemented in July 2001. With the help of co-integration and error correction model, the study reveals the presence of long run relation between the BSE Sensex and select macroeconomic indicators viz., Exchange Rate, Wholesale Price Index, T-bill rates and M3. Keywords: Macroeconomic indicators, stock returns, Cointegration JEL Classification: G15